Vascular access in children requiring maintenance haemodialysis: a consensus document by the European Society for Paediatric Nephrology Dialysis Working Group - Shroff, Rukshana; Schmitt, Claus P.; Heckert, Karlheinz (Nephrology, dialysis, transplantation, 2019)
AbstractBackground. There are three principle forms of vascular access available for the treatment of children with end stage kidney disease (ESKD) by haemodia